Enhancing the activity of pectinase using pulsed electric field (PEF) treatment. (July 2017) - Zhang, Fusheng; Tian, Meiling; Du, Muying; Fang, Ting
Abstract: Pectinase is commercially important in the fruit processing and fiber degumming industries. Emerging technologies that improve its stability and activity could have potential in improving its commercial value further. The effects of pulsed electric field (PEF) treatment on the enzymatic activity, kinetics and conformational structure of pectinase were evaluated. Maximum activity was obtained at 12 kV/cm and a flow velocity of 80 mL/min, and was 21.89 ± 1.67% higher than the untreated enzyme. This enhancing effect could be maintained for 19 h when the treated enzyme was stored at 4 °C. PEF treatment increased the enzyme kinetic constants V max, k cat, t 1/2, ΔG, and decreased K m, k, Ea, ΔH, and ΔS, indicating improved affinity between enzyme and substrate and enhanced catalytic efficiency. PEF treatment did not alter the polypeptide composition of the pectinase molecules, but induced the transfer of the tryptophan micro-environment from the polar surface to the hydrophobic interior, with a 10.28% increase in α-helices and a 17.80% reduction in random coils. Highlights: PEF enhanced pectinase activity and thermostability. The enhancing effect can maintain for 19 h when stored at 4 °C. PEF led to an increase in V max, k cat, t 1/2, ΔG and a decrease in K m, k, Ea, ΔH, ΔS of pectinase. PEF altered pectinase advanced structure, but hardly changed primary structure.